Thermal and cardiovascular responses and thermal sensation during hot-water bathing and the influence of room temperature. (May 2019) - Masuda, Yuta; Marui, Shuri; Kato, Issei; Fujiki, Mayuka; Nakada, Mariko; Nagashima, Kei
Abstract: The aim of the present study was to clarify physical risks during hot-water bathing by measuring thermal and cardiovascular responses and thermal sensation. Young men and women (n = 7 and 5, respectively) participated in the present study, which consisted of two trials mimicking bathing behavior at room temperature of 25 °C and 15 °C. Participants bathed in 41 °C water for 20 min to the subclavian level. Before bathing, participants rested fully clothed for 15 min and then rested for 15 min without clothes. After bathing, they rested without clothes for 15 min and afterwards rested fully clothed for another 15 min. Tympanic temperature (Tty ), heart rates (HR), mean skin temperature (Tsk ), mean arterial pressure (MAP), and laser-Doppler flow at the chest and forehead (LDFhead and LDFchest ) were evaluated. Thermal perception was assessed with a visual analogue scale. Mean Tsk in the 15 °C trial decreased during the period without clothing while MAP increased. The value remained unchanged in the 25 °C trial. During bathing, Tty, mean Tsk, HR, LDFhead, and LDFchest increased in both trials, and MAP decreased to similar levels. Relative change in LDFchest was greater in the 15 °C trial than in the 25 °C trial. Participants felt cold when they were without clothes at 15 °C; however, the thermal perception during bathing was similar between the two trials. Greater changes in cardiovascular and thermal responses were observed during the bathing behavior. In addition, bathing in cold room augmented the changes, which may induce some physical risks during bathing. Highlights: We experimentally assessed physical risks associated with bathing behavior. Participants rested before and after 41 °C water bathing in a room at 25 °C or 15 °C. Resting in a room at 15 °C increased blood pressure with reduction of skin temperature. Blood pressure decreased after bathing, which was augmented in a room at 15 °C.